The Inner (and Unavoidable?) Violence of Reason: Re‐reading Heidegger via Education. Issue 3 (24th November 2014) - d'Agnese, Vasco
<x xml:space="preserve">Abstract</x> Since Plato, Western thought has framed knowing as a method within 'some realm of what is' and a predetermined 'sphere of objects'. The roots and the consequences of this stance towards reason and truth were noted by Heidegger, who equates the history of Western thought with the history of metaphysics. Since Plato, truth has relied on definition, hierarchy and mastery. Discourse on the truth begins to be discourse on the limits of things and, thus, on who is able to set these limits and discourse. This dominant position erases its own traces, presents itself as unique and unavoidable, and excludes all other ways of thinking. This exclusion includes violence, and this violence is not merely a philosophical matter. It is written in the history of the West, which is a history that includes conquest, genocide and war. However, we can also identify in Heidegger ways to transcend this inner violence by returning to the originating stance towards truth, namely, truth as aletheia, or world disclosure. This article provides the groundwork to argue that Heidegger's thought, based on a call for existential responsibility, requires education to remake our existence.